Multi-modal sensing array for soft robots - Su, Jiangtao (Nanyang Technological University, 2025)
Soft robots, known for their flexibility and adaptability, are poised to revolutionize applications requiring gentle interaction with humans and delicate environments. Despite their potential, the development of soft robots has been limited by the disparity in adaptability and dexterity compared to natural organisms, due to a lack of advanced sensing technologies. Draws inspiration from the sensing mechanisms of biological entities, this thesis presents advancements in the field of sensing in soft robotics, addressing key challenges related to multi-modal sensory integration, high-density tactile sensing, and edge perception.